Inhibited Carnitine Synthesis Causes Systemic Alteration of Nutrient Metabolism in Zebrafish - Li, Jia-Min; Li, Ling-Yu; Qin, Xuan; Degrace, Pascal; Demizieux, Laurent; Limbu, Samwel M.; Wang, Xin; Zhang, Mei-Ling; Li, Dong-Liang; Du, Zhen-Yu (Frontiers in Physiology, 2018)
Impaired mitochondrial fatty acid β-oxidation has been correlated with many metabolic syndromes, and the metabolic characteristics of the mammalian models of mitochondrial dysfunction have also been intensively studied. However, the effects of the impaired mitochondrial fatty acid β-oxidation on systemic metabolism in teleost have never been investigated. In the present study, we established a low-carnitine zebrafish model by feeding fish with mildronate as a specific carnitine synthesis inhibitor (0.05% body weight (BW) /d) for 7 weeks, and the systemically changed nutrient metabolism, including carnitine and triglyceride (TG) concentrations, fatty acid (FA) β-oxidation capability, and other molecular and biochemical assays of lipid, glucose and protein metabolism, were measured. The results indicated that mildronate markedly decreased hepatic carnitine concentrations but not in muscle carnitine concentrations. Liver TG concentrations increased by more than 50% in mildronate-treated fish. Mildronate decreased the efficiency of liver mitochondrial β-oxidation, increased the hepatic mRNA expression of genes related to FA β-oxidation and lipolysis, and decreased the expression of lipogenesis genes. Mildronate decreased whole body glycogen content, increased glucose metabolism rate, and upregulated the expression of glucose uptake and glycolysis genes. Mildronate also increased whole body protein content and hepatic mRNA expression of mechanistic target of rapamycin (mtor), and decreased the expression of a protein catabolism-related gene. Liver, rather than muscle, was the primary organ targeted by mildronate. In short, mildronate-induced hepatic inhibited carnitine synthesis in zebrafish caused decreased mitochondrial FA β-oxidation efficiency, greater lipid accumulation, and altered glucose and protein metabolism. This reveals the key roles of mitochondrial fatty acid β-oxidation in nutrient metabolism in fish, and this low-carnitine zebrafish model could also be used as a novel fish model for future metabolism studies.